Die Mosaiken der Acheiropoietos-Basilika in Thessaloniki : Eine vergleichende Analyse dekorativer Mosaiken des 5. und 6. Jahrhunderts - Fourlas, Benjamin (Berlin/Boston De Gruyter, 2012)
The volume examinesfurther questions on the early Byzantine mosaics in the metropolis, and in particular their problematic chronology. A number of mosaics from the entire Mediterranean, which have to date received little attention, are also taken into account.
German
Keywords: Ancient history: to c 500 CE; Medieval history; Classical Greek & Roman archaeology; Acheiropoietos-Basilica; Ornamentation; Thessaloniki; Decorative Mosaics of the 5th to 7th Centuries